Cover Image, Volume 76, Issue 8. Issue 8 (9th July 2020) - Van den Eynde, Renik; Van Leeuwen, Thomas; Haesaert, Geert
Abstract : The cover image is based on the Review Identifying drivers of spatio‐temporal dynamics in barley yellow dwarf virus epidemiology as a critical factor in disease control by Renik Van den Eynde et al., https://doi.org/10.1002/ps.5851 . Abstract : The cover image is based on the Review Identifying drivers of spatio‐temporal dynamics in barley yellow dwarf virus epidemiology as a critical factor in disease control by Renik Van den Eynde et al., https://doi.org/10.1002/ps.5851 .